Fluids Through Inclined Granular Media (Global Journal of Science Frontier Research, 2017)
A theoretical analysis of inclined fluids through granular media was carried out. Modified Darcy's equation and its approximate solution showed that for the isothermal case, increase in the argument and permeability of the granules result in a corresponding increase in the pressure exerted on the photosphere while increase in porosity and viscosity brings about a decrease in the pressure. For the adiabatic fluid case, the pressure is not affected as a result of increase in the angle of the granules. The same physical results occur in both the isothermal fluid case and that of the adiabatic fluid case as a result of increase in viscosity, porosity and permeability of the granules in the pressure exerted on the photosphere.
Keywords: granules; isothermal; adiabatic; photosphere; darcy’s equation; taylor’s series expansion